Recent advances in fetal alcohol spectrum disorder for mental health professionals. Issue 4 (July 2019) - Mela, Mansfield; Coons-Harding, Kelly D.; Anderson, Tara
Abstract : Purpose of review: Understanding the pathophysiologic, diagnostic, and treatment implications of the interface between mental disorder and the consequences of Prenatal Alcohol Exposure (PAE) is important for mental health professionals (MHP) seeking to provide the most effective care. This review was written to highlight the importance of identifying and intervening with regards to the unique mental health and medical needs of individual with PAE. Recent findings: Over the last year, research has identified differences in the diagnostic criteria for Neurodevelopmental Disorder Associated with PAE (ND-PAE)/Fetal Alcohol Spectrum Disorder (FASD) and called for standardization, given that diagnosis is the main route to appropriate support. Care will improve with advances in epigenetic, neuroimaging, and electrophysiological discoveries regarding the consequences of PAE. For example, recent progressions allow for improved detection of alterations in DNA methylation and functional connectivity between cortical and deep grey matter. Therapeutic innovations targeting specific neurocognitive impairment and ligand-specific symptom clusters, as well as lifelong multidisciplinary interventions to support patients, were reported as producing effective outcomes. Summary: Developments in genetics, epigenetics, imaging, and interventions are relevant to the current knowledge of FASD. MHP are encouraged to recognize the importance of understanding unique considerations for this population, including forensic implications and the whole-body impacts of FASD, which could assist in reducing stigma and improving quality of care.